KAJIAN KARAKTERISTIK VISUAL MELALALUI PENDEKATAN ESTETIKA TERHADAP MOTIF TEBAR MENGKUDU SANGGAR BATIK BETAWI TEROGONG - Putra, Damar Rangga (International Conference on Humanity Education and Society (ICHES), 2024)
This paper discusses the aesthetic study using Monroe C. Beardsley's theory of aesthetics in Betawi batik motifs developed by Sanggar Batik Terogong. Beardsley on Betawi batik pattern developed by Sanggar Batik Terogong. This studio was chosen because there are still few studies on Betawi batik that discuss this studio. The purpose of the research is to map and look for characteristics based on aesthetic theory. This research uses a Qualitative approach that is concluded descriptively. The data collection techniques were observation, interview and document review. The theory used in this research is Aesthetic Theory which explains three aesthetic values, namely Unity, Complexity, and Intentionality. The results showed that there are no standard rules in making Betawi batik pattern in Sanggara terogong, but there are unique characteristics of craftsmen in making Tebar Mengkudu Betawi Batik pattern.